2020
DOI: 10.1007/s00296-020-04653-x
|View full text |Cite
|
Sign up to set email alerts
|

Monogenic lupus due to spondyloenchondrodysplasia with spastic paraparesis and intracranial calcification: case-based review

Abstract: Spondyloenchondrodysplasia (SPENCD) is a rare skeletal dysplasia characterized with platyspondyly and metaphyseal lesions of the long bones mimicking enchondromatosis, resulting in short stature. SPENCD often coexists with neurologic disorders and immune dysregulation. Spasticity, developmental delay and intracranial calcification are main neurologic abnormalities. Large spectrum of immunologic abnormalities may be seen in SPENCD, including immune deficiencies and autoimmune disorders with autoimmune thrombocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 40 publications
(68 reference statements)
0
21
0
Order By: Relevance
“…It has also been shown that increased osteopontin has an important role in the pathogenesis of albuminuria by acting on renal podocytes, as shown in diabetic patients (possibly increasing glomerular damage through TGF-beta expression) 21 . In addition, since clinical findings may occur at different ages in the same family, even in patients with the same ACP5 gene mutation 22 , immunological and skin findings related to SLE may occur in our patients in the coming years.…”
Section: Discussionmentioning
confidence: 86%
“…It has also been shown that increased osteopontin has an important role in the pathogenesis of albuminuria by acting on renal podocytes, as shown in diabetic patients (possibly increasing glomerular damage through TGF-beta expression) 21 . In addition, since clinical findings may occur at different ages in the same family, even in patients with the same ACP5 gene mutation 22 , immunological and skin findings related to SLE may occur in our patients in the coming years.…”
Section: Discussionmentioning
confidence: 86%
“…A wide spectrum of immune dysregulation associated with SPENCDI has been described, including development of SLE. Neurological manifestations include developmental delay, spastic paresis, and intracranial calcifications ( 149 ). Mutations in PSMB8 is a cause of a disorder previously called chronic atypical neutrophilic dermatosis with lipodystrophy and elevated temperature (CANDLE).…”
Section: Autoinflammatory Disordersmentioning
confidence: 99%
“…1 Vasculitis, renal involvement and autoimmune hypothyroidism are also reported as a continuum of this spectrum. 4,5 Immune dysregulation predisposes to an immunodeficient state characterized by hypogammaglobulinemia and low B-, T-and NK-cell counts causing recurrent pneumonia, disseminated herpes zoster and skin and dental abscesses. 6 Neurological manifestations include developmental delay, spasticity, ataxia, psychosis, abnormal movements and painful multifocal neuropathy.…”
Section: Letter To the Editormentioning
confidence: 99%